Kebijakan Kebijakan Pemerintah Daerah dalam Pengembangan Pariwisata Kawasan Rawan Bencana di Desa Ban, Kabupaten Karangasem, Bali - Sanjiwani, Putri Kusuma; Kerti Pujani, Luh Putu (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
Karangasem Regency has Mount Agung which is included in one of the active volcano clusters in Indonesia, so it has a significant disaster risk if it used as a tourist attraction. Desa Ban is one of the villages within the radius of the Gunung Agung Disaster Prone Area. Desa Ban must get different treatment if it is developed as a tourist attraction.This research was conducted to determine the form of Local Government policies in the development of tourism in the Volcano Disaster Prone Areas in Ban Village, Karangasem Regency.The research method in this study uses the empirical legal method in studying and looking at the law in terms of tourism. Analyze the problem based on authority theory, functional theory, policy concepts, agrotourism concepts and decentralization principle. Using legal analysis techniques and legal evaluation in Local Government policy making. The results of this study are the policy of developing agrotourism as an ideal tourism business that can be carried out in the volcano prone areas. This policy is related to the limitation of tourism activities to reduce the risk of volcano natural disasters so that the loss of the community or minimizing disaster victims can be reduced if the eruption occurs in an unexpected time.